Perilaku Bullying pada Remaja di Karawang: Peran Kontrol Diri dan Konformitas - Friska Faradilla Andriani; Puspa Rahayu Utami Rahman; Dinda Aisha (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the influence of self-control and conformity on the tendency of bullying among adolescents in Karawang Regency. The study employed a quantitative approach with a causal design. The sample consisted of 204 adolescents aged 12–18 years, selected using a convenience sampling technique. The instruments used were the Olweus Bullying Questionnaire (OBVQ-R), the Brief Self-Control Scale (BSCS), and the Conformity Scale. Data were analyzed using multiple linear regression with SPSS. The partial test results showed that the significance value of X1 was 0.000 < 0.05, indicating that Ha1 was accepted and H01 was rejected, meaning that self-control has an influence on the tendency of bullying. The significance value of X2 was 0.027 < 0.05, indicating that Ha2 was accepted and H02 was rejected, meaning that conformity has an influence on the tendency of bullying. The simultaneous test results showed a significance value of 0.000 < 0.05, indicating that Ha3 was accepted and H03 was rejected, which means that self-control and conformity jointly influence the tendency of bullying. The findings demonstrated that the significance value was 0.000 (p < 0.05), meaning that Ha was accepted and H0 was rejected. Thus, self-control and conformity significantly influence the tendency of bullying. The effect size of 13.1% indicates that these two variables together are able to explain the variation in the tendency of bullying.